Community-Based Approaches to Combating Desertification - Haydarov Hasanjon Hakimovich; Kushimov Bakhtiyor Alishovich (Peerian Journals Publishing, 2023)
Desertification, a significant environmental challenge, threatens the sustainability of ecosystems and livelihoods worldwide. This scientific article presents a comprehensive analysis of community-based approaches to combating desertification. The study explores the key concepts, discusses relevant literature, outlines the methodology employed, presents the results, engages in a thorough discussion, and concludes with implications for future research. The findings highlight the effectiveness of community engagement, participation, and empowerment in fostering sustainable land management practices. Community-based approaches prove to be instrumental in mitigating desertification and promoting environmental resilience
Keywords: desertification; community-based approaches; sustainable land management